2023
DOI: 10.1021/acs.jafc.2c08076
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota Mediates Lactobacillus rhamnosus GG Alleviation of Deoxynivalenol-Induced Anorexia

Abstract: Deoxynivalenol (DON) is a widespread mycotoxin and causes anorexia and emesis in humans and animals; Lactobacillus rhamnosus GG (LGG), a well-characterized probiotic, can improve intestinal barrier function and modulate immune response. Currently, it is unclear whether LGG has a beneficial effect on DON-induced anorexia. In the present study, mice were treated with DON, LGG, or both by gavage for 28 days to evaluate the effects of LGG on DON-induced anorexia. Antibiotic treatment and fecal microbiota transplan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 79 publications
(145 reference statements)
0
6
0
Order By: Relevance
“…However, oral supplementation with LGG and/or tributyrin effectively mitigated these losses [ 53 , 58 ]. Notably, the administration of LGG also augmented the production of butyric acid in cecal contents, which attenuated deoxynivalenol (DON)-induced inflammation and impairment of the intestinal barrier function [ 66 ]. These effects collectively contribute to enhancing the function of the intestinal barrier.…”
Section: Discussionmentioning
confidence: 99%
“…However, oral supplementation with LGG and/or tributyrin effectively mitigated these losses [ 53 , 58 ]. Notably, the administration of LGG also augmented the production of butyric acid in cecal contents, which attenuated deoxynivalenol (DON)-induced inflammation and impairment of the intestinal barrier function [ 66 ]. These effects collectively contribute to enhancing the function of the intestinal barrier.…”
Section: Discussionmentioning
confidence: 99%
“…Larger animals have more human-like anatomy and physiology, but are more expensive and require more space. As a result, mice are often selected to perform 28-day oral toxicity studies [ 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…As our data indicated, gut microbiota α-diversity was higher in LGG sows when compared to CON sows, consistent with research showing that LGG enhanced α-diversity in an insulin resistance mouse model [ 41 ]. Previous reports also showed that individuals with insulin resistance had lower Lactobacillus abundance [ 42 , 43 ], which could be increased by LGG [ 44 ]. Consistent with these observations, we identified higher Lactobacillus abundance in LGG sows.…”
Section: Discussionmentioning
confidence: 99%